Portable Library Automation Systems Implementation and Training in an Elementary School - Gunawan, Daisy Christina; Gunawan, Samuel Theodore; Agustin, Charles; Putra, Jeremy Triutomo; Darmawanto, Gabrielle Orla; Kinantya, Valereyna Jingga; Bhakti, Muhammad Agni Catur; Djajasoepena, Rafie; Wandy, Wandy (Center for Research and Community Service of Sampoerna University, 2023)
School libraries play a crucial role in literacy development by providing reading materials to students. Implementing library automation systems is an effective solution, enabling simplified cataloging, circulation control, and reporting. Automated systems streamline resource management and expand user access. The Senayan Library Management System (SLiMS), a freely available program developed to streamline library processes, is recognized as a potential option for enhancing a school's library feature and developing educational institution assets. The objectives of this community service were to implement a library automation system to enhance the school library features and services. Also, this activity was for system implementation experiences for the higher students. The community service initiatives were carried out in the SDN Gadog 2, Indonesia, between September and October of 2023. This concludes that SLiMS was successfully implemented, trained, and helpful as it enhances the flexibility of borrowing and accessing books.